Osmocote® promotes positive responses in the growth and nutrition of Lecythis lurida seedlings (Lecythidaceae) - Jardim, Iselino Nogueira; Oliveira, Jeferson Coutinho de; Hamada, Márcia Orie de Sousa; Oliveira, Israel Alves de (Revista de Ciências Agroveterinárias, 2024)
The success of reforestation projects for commercial and environmental purposes depends, among other factors, on the availability of nutrients during seedling production. Currently, controlled-release fertilizer is widely used because it provides quality seedlings. The objective of the study was to evaluate the efficiency of Osmocote® fertilizer in the initial growth and nutrition of Lecythis lurida seedlings. The seedlings were produced from seeds collected from mother trees in the municipalities of Vitória do Xingu and Altamira, state of Pará. Sowing was carried out in plastic bags with a capacity of 1 dm3, filled with coconut fiber substrate plus dded with doses of Osmocote® fertilizer. The experimental design adopted was completely randomized with a single factor (dose of Osmocote®) distributed into five doses: 0.0 (control); 2.0; 4.0; 6.0 and 8.0 g L-1 of Osmocote® fertilizer. For each treatment, 20 replications were used (one plant per replication). At 120 days after emergence, morphological parameters were evaluated to determine the growth of the seedling and nutritional analysis of the leaves. The dose of Osmocote® that provided the best response to morphological variables was 6.0 g L-1. The macro (micronutrients) extracted and exported by the Lecythis lurida seedling in g kg-1 (mg kg-1) were in the following order: K>N>Mg>S>Ca>P>(Fe>Mn>Zn>B>Cu). It is concluded that dose 6.0 g L-1 of Osmocote® improved the nutrition and quality of Lecythis lurida seedlings. The use of Osmocote® fertilizer allows greater growth and better nutritional status for Lecythis lurida seedlings.